Controversies in Tourism - Moufakkir, Omar (CABI, 2014)
Tourism is a dynamic global phenomenon: an agent of change, harbinger of controversy, and a significant factor in social, cultural and technical evolution. Such evolutions, especially those driven by tourism, are almost certainly followed by a variety of induced controversies. In order to gain fur- ther insight into how societies and cultures work and interact, critical analysis of the contexts, causes and consequences of the controversies is required. Failure to com- prehend the basis of a tourism controversy may (more than not) produce myopic tour- ism development policies of the sort seen in countries ranging from Turkey to Kenya. At worst, failure to recognize and deal with controversy can lead to the systemic failure of tourism to meet the expectations of inves- tors, politicians and citizens.